(untitled) (The South East European Journal of Economics and Business, 2022)
This paper explores the political and economic determinants of remittance transfers by foreign workers in hosting countries with an application to the case of the Gulf Cooperation Council (GCC) countries. Our empirical model is estimated with the fixed-effects technique applied on annual data covering the period 1996-2019. The main result confirms that both the economic and political stability do matter to remittance transfers. First, our findings suggest that higher per capita growth across the GCC region tends to discourage remittance transfers. Second, we find a statistically significant and positive relationship between oil prices and remittance transfers. Third, our findings show that political stability across the host countries can shape remittances. Put it simply, higher political stability tends to induce lower remittance outflows. While conventional findings on importance of economic factors for remittances are confirmed, this research signifies that any change in political stability across the GCC might affect decisions made by foreign workers. This finding has general implications for similar regions throughout the world suggesting that political stability has a strong effect on the flow of remittances.